Doppelbegabung im Expressionismus - zur Beziehung von Kunst und Literatur bei Oskar Kokoschka und Ludwig Meidner - Dorle, Meyer (Universitätsverlag Göttingen, 2013)
Double-talented artists were particularly numerous during the period of expressionism, which was characterized by political and radical social changes. The book presented offers informations about the artists' motivations and focuses on two excellent examples of artistic double-talent - Oskar Kokoschka, the founder of drama expressionism and Ludwig Meidner, highly praised for his apocalyptic landscapes. The interdisciplinary comparison of paintings and graphics with the dramas, poems and prose texts written by the artists allows offers valuable insights into their entire expressionistic oevre and, at the same time, a closer understanding of the relationship between art and literature.